Penelitian Determinan Tindak Pencegahan Fraud Pengelolaan Dana Desa di Kecamatan Penukal Utara Kabupaten PALI - Agnes Rafiva Nanda Utami; Maria; Indra Satriawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the Determinants of Fraud Prevention in Village Fund Management in North Penukal District, PALI Regency. The population in this study were 13 villages in North Penukal District, Penukal Abab Lematang Ilir Regency. The data collection technique used a questionnaire with respondents Village officials consist of the Village Financial Management Power Holder (PKPKD) is the village head, while the Village Financial Management Implementers (PPKD) are the village secretary, village treasurer, administrative and general head, planning head, government head, welfare head and service head. Based on the results of the study, the competence of village officials, internal control system, whistleblowing system and organizational commitment partially and simultaneously have a positive and significant effect on preventing fraud in village fund management. The Adjusted R Square value is 0.371, which means that the competence of village officials, internal control systems, whistleblowing systems and organizational commitment have an effect of 37.1% on preventing fraud in village fund management.